2019
DOI: 10.1371/journal.pone.0223596
|View full text |Cite
|
Sign up to set email alerts
|

CavBench: A benchmark for protein cavity detection methods

Abstract: Extensive research has been applied to discover new techniques and methods to model protein-ligand interactions. In particular, considerable efforts focused on identifying candidate binding sites, which quite often are active sites that correspond to protein pockets or cavities. Thus, these cavities play an important role in molecular docking. However, there is no established benchmark to assess the accuracy of new cavity detection methods. In practice, each new technique is evaluated using a small set of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…In detail, FPocket alone was able to recognize one half of the correct pockets (20 out of 40, precision = 0.50), a performance which is in line with that reported by the above mentioned benchmarking study for FPocket when used without repetitions [10]. The performances of docking scores alone are slightly worse than those reached by FPocket (18 out of 40, precision = 0.45) even though it should be noted that docking simulations are not blindly performed on all the protein surfaces but they are focused on the pockets previously detected by FPocket and thus the docking performances unavoidably benefit (at some extent) of the encouraging results offered by FPocket.…”
Section: Pockets 20 Performancessupporting
confidence: 89%
See 1 more Smart Citation
“…In detail, FPocket alone was able to recognize one half of the correct pockets (20 out of 40, precision = 0.50), a performance which is in line with that reported by the above mentioned benchmarking study for FPocket when used without repetitions [10]. The performances of docking scores alone are slightly worse than those reached by FPocket (18 out of 40, precision = 0.45) even though it should be noted that docking simulations are not blindly performed on all the protein surfaces but they are focused on the pockets previously detected by FPocket and thus the docking performances unavoidably benefit (at some extent) of the encouraging results offered by FPocket.…”
Section: Pockets 20 Performancessupporting
confidence: 89%
“…Moreover, the increasing number of experimentally resolved protein structures allows a markedly more accurate validation of these methods [9]. By using a purposely collected cavity database, a recent benchmarking analysis compared some well-known approaches for mapping the protein cavities and revealed that FPocket and GaussianFinder are those offering the best performances, with FPocket being able to identify the highest number of correct cavities [10].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that, contrary to historical belief, apo structures can perform as well as, or better than, holo structures. Previous studies have been mixed on the issue of apo versus holo structures 5,6,22 , and the behavior described here is attributed specifically to our dataset. Our complete data for this manuscript is provided in the Supplementary Information covering all calculated P, R, F, and MCC value for all individual PDB structures (Table S1 in the Supplementary Information) and giving median MCC and median F for the whole protein families (Table S2).…”
Section: Discussionmentioning
confidence: 97%
“…Only Fpocket (p = 0.03) has a statistically significant (p < 0.05) correlation between predictive power and structure type (holo vs. apo), again suggesting that holo structures perform slightly better with this method, but the trend is weak. CavBench's assessment showed equal performance of Apo and Holo protein structures in non-redundant binding site detection for Fpocket and for Ghecom 22 .…”
Section: Lbs Predictionmentioning
confidence: 99%
See 1 more Smart Citation